2021
DOI: 10.1097/scs.0000000000008326
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Blink Analysis in Patients With Established Facial Paralysis Using High-Speed Video Analysis

Abstract: This study analyzed the blink characteristics of patients with incomplete and complete facial paralysis. The authors measured and compared the palpebral distance, eyelid movement distance, and the eye-closing ratio of blinks in 55 patients with Bell's palsy or Ramsay Hunt syndrome (Bell & Hunt group) and 14 with complete paralysis (Complete Paralysis group). in the Bell & Hunt group, the palpebral distance (7.94 mm) was smaller on the paralyzed side than on the non-paralyzed side (9.61 mm). The eyeclosing rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The limitation of this study is the lack of combined lower eyelid in blink measurement in accordance with Ogawa's study (14). Another limitation is that aberrant regeneration should be also considered such as hemifacial spasm, eye fissure narrowing during facial movement, and simple brow ptosis, even though we tried to exclude the patient in this study.…”
Section: Discussionmentioning
confidence: 89%
“…The limitation of this study is the lack of combined lower eyelid in blink measurement in accordance with Ogawa's study (14). Another limitation is that aberrant regeneration should be also considered such as hemifacial spasm, eye fissure narrowing during facial movement, and simple brow ptosis, even though we tried to exclude the patient in this study.…”
Section: Discussionmentioning
confidence: 89%
“…25 Another study on 55 patients with Bell's palsy or Ramsay Hunt syndrome found that the PA and movement of the eyelids on the affected side were significantly reduced compared to the unaffected side. 26 Blink dynamics in CPEO patients have been less investigated thorough the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Both preoperative and postoperative photography and video assessment can provide invaluable data for the surgeon 19–21 . Video documentation 20,21 allows for assessment of the dynamic movements and evaluation of asymmetry and synkinesis.…”
Section: Imaging and Videographymentioning
confidence: 99%
“…Both preoperative and postoperative photography and video assessment can provide invaluable data for the surgeon. [19][20][21] Video documentation 20,21 allows for assessment of the dynamic movements and evaluation of asymmetry and synkinesis. Videotaping should be done with the patient seated and ideally with a head restraint to minimize lateral movement.…”
Section: Imaging and Videographymentioning
confidence: 99%